EVALUASI PEMBELAJARAN DARING TERHADAP MATA KULIAH STATISTIKA IPA IAIN BENGKULU - Nahdiyah Sakina; Sri Nurmawati; Yuni Sarawati; Ahmad Walid (Academy of Education Journal, 2021)
This study aims to explain the evaluation of online learning of IAIN Bengkulu's science statistics course. This study uses a descriptive method with a design in the form of a google form, the study involved 20 students of the 5th semester of IAIN Bengkulu's IPA who had taken statistics courses. This study uses data evaluation techniques by calculating the percentage of data from each aspect of the indicators of the questions that exist. The results of this study indicate that the online learning evaluation of the 5 semester IAIN Bengkulu statistics course obtained an average percentage score of 48.7% with agreed criteria. From this, it is hoped that the reader will make the results of this study an evaluation or learning that will be carried out further regarding the learning of statistics courses.